PERAN PPID BAWASLU DALAM MEWUJUDKAN PELAYANAN PUBLIK YANG TRANSPARAN DAN AKUNTABEL MELALUI PELAYANAN INFORMASI PUBLIK - Ferry Bashanova; Muhammad Aini (JOURNAL OF LAW AND NATION, 2026)
Public information service constitutes an integral component of public service delivery and serves as an important instrument in promoting transparency, accountability, and public participation in democratic governance. As a public institution responsible for supervising electoral processes, the Election Supervisory Agency (Bawaslu) is obligated to provide accessible and accountable public information services to the community. This responsibility is implemented through the Information and Documentation Management Officer (PPID), which manages, documents, and disseminates public information in accordance with applicable regulations. This study aims to analyze the role of PPID within Bawaslu in realizing transparent and accountable public services through public information services, examine the management of exempted information, and identify potential challenges in its implementation. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that PPID plays a strategic role in supporting transparency and accountability by ensuring public access to information related to institutional activities, election supervision, violation handling, and dispute resolution processes. Furthermore, the management of exempted information represents an essential aspect of public information services because it seeks to balance public access to information with the protection of legal interests, personal data, and ongoing law enforcement processes. The study also reveals several implementation challenges, including differing interpretations regarding information classification, public information disputes, personal data protection issues, digital information security concerns, and varying levels of public information literacy. Therefore, strengthening institutional capacity, improving human resource competence, enhancing digital information governance, and increasing public awareness regarding information disclosure are essential to improving the quality of public services within Bawaslu.